"Voluntary Return" without Civil Society?: How the Exclusion of Nongovernment Actors from the Austrian and British Return Regimes Affects the Quality of Voluntariness. Issue 1 (1st June 2022) - Schweitzer, Reinhard
Abstract: This article looks at the implementation of so-called "assisted voluntary return" policies in Austria and Britain, where state agencies have recently replaced nongovernmental organizations as providers of return counseling. To better understand how such a shift affects the in/voluntariness of return, I identify three dimensions along which the "quality" of voluntariness can be assessed and relate them to concrete aspects of return counseling practice: absence of coercion; availability of acceptable alternatives; and access to adequate and trusted information. Based on original qualitative data, I show that even within an overall restrictive and oppressive regime, return counselors can make room for voluntariness by upholding ethical and procedural standards—if they retain substantial independence from the government.